ARBITRARY ORDER RECURSIVE SEQUENCES AND ASSOCIATED CONTINUED FRACTIONS - Shannon, Anthony G; Cook b, Charles K; Hillman c, Rebecca A. (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
The essential idea in this paper it to generalize and synthesize some of the pioneering ideas of Bernstein, Lucas and Horadam on generalizations of basic and primordial Fibonacci numbers and their arbitrary order generalizations and their relation to generalized continued fractions with matrices as the unifying elements.